Book Review – Bell’s Diarrhoea (Advancements in Homeopathic Research, 2022)
This is a book review which tries to throw light on a very precious clinical repertory Bell’s Diarrhoea which is now a days not used by practioners as it is not included in softwares of repertory. This article analysis the Philosophy, construction, adaptability along with merits and demerits of Bells diarrhoea and shows that in acute Gastroenteritis, it can serve as one of the clinical bedside Repertory on Diarrhoea and can be used and it is very effective to reach the simillimum and help to cure the case.
Keywords: Gastroenteritis; Bell’s Diarrhoea